Forms of State intervention in the face of changes in the communication industries : the logic of actors around universal service in Senegal - (:unkn) unknown (My University, 2022)
In this present work I study the policy of the "universal service" of telecommunications in Senegal. It is a question of dealing with the issues that revolve around this notion as well as the logic of the actors who hide behind it. Indeed, the implementation of this "universal service" policy in Senegal and in several West African countries suggests a new form of State interventionism in the telecommunications sector, while a of the reasons for re-regulation, introduced in the 1980s in Francophone West Africa by international financial institutions through structural adjustment policies, was to promote the disengagement of the nation-state from the sphere of production .Through this perspective, we postulate that the more a State is forced to delegate resources and transfer powers to the private sector (deconcentration of powers), the more it seeks to put in place instruments enabling it to adapt to these constraints by seeking to have a mastery of the actors of this sector and the resources that the latter generates (re-concentration of powers).In this context, we want to defend, through this work, the thesis according to which this movement of deconcentration/re-concentration of power would be based, in particular, on the implementation of communication strategy and variation of intentionalities around the notion of “universal service” which would constitute in this sense both a mode of action for the political authorities and an instrument for legitimizing public action. In this sense, we wish to place our problem in the perspective of research released by Armand Mattelart on the challenges of communication.We used thematic content analysis to exploit our corpus composed of written documents and interviews in order to verify our hypotheses.
Keywords: African Research